Characterization of early cortical population response to thalamocortical input in vitro - Hill, Michael R.; Greenfield, Susan A. (Frontiers in Neuroscience, 2014)
The in vitro thalamocortical slice preparation of mouse barrel cortex allows for stimulation of the cortex through its natural afferent thalamocortical pathway. This preparation was used here to investigate the first stage of cortical processing in the large postsynaptic dendritic networks as revealed by voltage sensitive dye imaging. We identified the precise location and dimensions of two clearly distinguishable dendritic networks, one in the granular layer IV and one in the infragranular layer V and VI and showed that they have different physiological properties. DiI fluorescent staining further revealed that thalamocortical axons project on to these two networks in the typical barrel like form, not only in the granular but also in the infragranular layer. Finally we investigated the short term dynamics of both the voltage sensitive dye imaging signal and the local field potential in response to a train of eight-pulses at various frequencies in both these layers. We found evidence of differences in the plasticity between the first two response peaks compared to the remaining six peaks as well as differences in short term plasticity between the voltage sensitive dye imaging response and the local field potential. Our findings suggest, that at least early cortical processing takes place in two separate dendritic networks that may stand at the beginning of further parallel computation. The detailed characterization of the parameters of these networks may provide tools for further research into the complex dynamics of large dendritic networks and their role in cortical computation.